Providing Insurance for Good Repayment Performance: The Individual Emergency Fund, Philippines - Niels Kemper; Markus Frölich; Pia Naima Unte (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Asymmetric information impairs the functioning of credit markets, in particular in developing countries where incomplete property rights and lack of collateral are a common joint occurrence. In such an environment financial institutions enable lending by transferring the responsibilities for the screening and monitoring of the borrowers as well as the enforcement of credit contracts, to the borrowers themselves to ease problems of asymmetric information. This comprises non-collateral based lending methodologies such as peer monitoring through co-signers (Klonner and Rai, 2010) and, especially, peer screening and monitoring in individual and joint liability group lending with the possibility to impose social sanctions (Gin and Karlan, 2014). In addition, improved personal identification through fingerprints may alleviate credit market imperfections (Gin et al., 2012). These approaches have in common that they rely on the punishment of non-compliance with credit contracts as principle enforcement mechanism, e.g. through legal action or social sanctions. They contrast with alternative mechanisms which reward compliance, rather than punishing non-compliance, with credit contracts. One example is dynamic incentives, i.e. offering bigger loans sizes to clients when the build up a positive credit history. Another example, and subject to this impact evaluation, is conditioning gratuitous insurance provision for the client through the financial institution on clients' good standing with the financial institution (clients are in good standing if they are neither in arrears nor completely defaulted on their loans). We evaluate the impact of such a conditional insurance provision on the repayment performances of microfinance clients in a Randomized Controlled Trial. The impact evaluation employs weekly data on the financial activities of roughly 22000 clients in 700 client centers from the management information system (MIS) of the microfinance institution. To evaluate the impact of the IEF on clients, we complement the weekly MIS data with weekly data on a subsample of 500 to 700 clients collected through phone surveys.
Keywords: D12; G21; O12; 330